Local heritage/ global forces: hybrid identities in Le Guin’s The Telling - Jamshidian, Sahar; Pourgiv, Farideh (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper examines Ursula K. Le Guin’s The Telling (2000), her last novel in the Hainish Cycle, which addresses intercultural communications among her imagined worlds. These relationships, which resemble those of our globalizing world, are analyzed in the light of Homi Bhabha’s theories of mimicry, hybridity and the Third Space. It is suggested that in this novel, Le Guin criticizes cultural imperialism and rejects both conservative and assimilative attitudes toward the other; instead, she praises hybridity as the culture of our globalizing world. Besides warning against the hegemony of the West in international relationships, through analogy, The Telling highlights the ways the developing countries could be responsible for their own colonialism and the annihilation of their own culture. In this context, this paper proposes that the Dovzans, lured by Hain’s advanced technology, as an act of self-colonization, impoverish their lives and deny their entire culture by criminalizing the Telling. The article further argues that indigenous peoples and groups of minorities, through hybridity and focus on their difference, not only can survive and conserve their local heritage and identity in the face of intense globalization pressures but also affect the dominant power. Accordingly, Sutty and the people of Okzat-Ozkat are introduced as courageous hybrid characters who finally succeed in asserting their voice in the third space. The article concludes that through bargaining with the Ekumen and remaining faithful to their own culture, the people of Okzat-Ozkat can save the Telling from extermination.